First checklist of mayflies (Insecta, Ephemeroptera) from Kosovo - Xërxa, Bardh L. (Zookeys, 2019)
Abstract. This research provides the first systematic contribution to the mayfly (Ephemeroptera) Fauna of Kosovo. This investigation was conducted from March to November in 2017 and 2018; 32 sites were sampled covering the different freshwater ecosystems of the country. The first checklist of mayflies of Kosovo is provided. During this survey, we found 48 species belonging to 20 genera and nine families. The highest number of species belongs to the following two families, Heptageniidae (24) and Baetidae (9). This investigation is a contribution to the knowledge about taxonomy, biogeography, and ecology of mayflies of the Balkan Peninsula by giving new data on species composition and distribution range in Kosovo.